The Existence of the Ma'arif Educational Institution (LP Ma'arif) of Nahdlatul Ulama in the City of Gunungsitoli - Suharni Polem; Yusnaili Budianti; Azizah Hanum OK (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The Ma’arif Nahdlatul Ulama Educational Institution (LP Ma’arif NU) is one of the key pillars in the development of Islamic education in Indonesia, oriented toward the values of Ahlussunnah wal Jama’ah (Aswaja) and the principle of religious moderation (wasathiyah). This study aims to describe the historical background of LP Ma’arif NU’s establishment in Gunungsitoli City, analyze its role in advancing Islamic education, and identify the challenges it faces in maintaining its existence amid local social and cultural dynamics This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews with LP Ma’arif NU administrators, school principals, teachers, and community leaders, as well as through field observations and documentation studies. Data analysis was conducted using data reduction, data presentation, and interactive conclusion-drawing techniques. The findings indicate that LP Ma’arif NU in Gunungsitoli City was established on the initiative of NU members to provide moderate Islamic education rooted in local traditions. The study concludes that LP Ma’arif NU in Gunungsitoli City plays a strategic role in strengthening moderate Islamic education but requires institutional reinforcement, stakeholder support, and adaptive strategies to grow and remain competitive in the future.